Cathepsin L regulates metabolic networks controlling rapid cell growth and proliferation - Weiss Sadan, T; Itzhak, G; Kaschani, F; Yu, Z; Mahameed, M; Anaki, A; Ben-Nun, Y; Merquiol, E; Tirosh, B; Kessler, B; Kaiser, M; Blum, G (American Society for Biochemistry and Molecular Biology, 2019)
Rapidly proliferating cells reshape their metabolism to satisfy their ever-lasting need for cellular building blocks. This phenomenon is exemplified in certain malignant conditions such as cancer but also during embryonic development when cells rely heavily on glycolytic metabolism to exploit its metabolic intermediates for biosynthetic processes. How cells reshape their metabolism is not fully understood. Here we report that loss of cathepsin L (Cts L) is associated with a fast proliferation rate and enhanced glycolytic metabolism that depend on lactate dehydrogenase A (LDHA) activity. Using mass spectrometry analysis of cells treated with a pan cathepsin inhibitor, we observed an increased abundance of proteins involved in central carbon metabolism. Further inspection of putative Cts L targets revealed an enrichment for glycolytic metabolism that was independently confirmed by metabolomic and biochemical analyses. Moreover, proteomic analysis of Cts L-knockout cells identified LDHA overexpression that was demonstrated to be a key metabolic junction in these cells. Lastly, we show that Cts L inhibition led to increased LDHA protein expression, suggesting a causal relationship between LDHA expression and function. In conclusion, we propose that Cts L regulates this metabolic circuit to keep cell division under control, suggesting the therapeutic potential of targeting this protein and its networks in cancer.